Incidence of Stroke in Young Adults: A Review - Carmine Marini; Tommasina Russo; Giorgio Felzani (Stroke Research and Treatment)
Introduction. Stroke in the young may have a dramatic impact on the quality of life in survivors. This study was aimed to evaluate incidence of first-ever stroke in the young by means of a systematic review. Materials and Methods. All papers on incidence of stroke in the young published after 1980, were identified by electronic search of Medline and manual search of reference lists. Only studies recruiting subjects under 44 years of age and with a lower age limit not higher than 20 years were included. Incidence rates were standardized to the 2000 European population according to the direct method. Poisson regression analysis was used to compare studies. Results. 29 studies including 3548 participants were identified. Incidence rates, after excluding a few outliers, ranged between 8.63 and 19.12 for crude rates and between 8.70 and 21.02 for standardized rates. Heterogeneity among studies was statistically significant but improved after excluding 4 studies. Few studies reported the proportions of stroke subtypes. Conclusions. Stroke in subjects under 45 years of age is not such a rare disease and requires specific preventive programs.